2015
DOI: 10.3390/s151025730
|View full text |Cite
|
Sign up to set email alerts
|

Non-Rigid Structure Estimation in Trajectory Space from Monocular Vision

Abstract: In this paper, the problem of non-rigid structure estimation in trajectory space from monocular vision is investigated. Similar to the Point Trajectory Approach (PTA), based on characteristic points’ trajectories described by a predefined Discrete Cosine Transform (DCT) basis, the structure matrix was also calculated by using a factorization method. To further optimize the non-rigid structure estimation from monocular vision, the rank minimization problem about structure matrix is proposed to implement the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Furthermore, the performance of our marker-less algorithm is illustrated on the Human3.6M. We compare our approach, which is denoted as TUNS (temporal union of nonlinear subspaces) in the remainder of this section, against six NRSfM baselines: point tracking algorithm PTA [ 5 ], the trajectory-sapce method CSF [ 6 ], the block matrix method BMM [ 8 ], the temporal union of subspaces TUS [ 31 ], the accelerated proximal gradient optimization APG [ 9 ] and the consensus NRSfM of CNR [ 14 ]. For PTA [ 5 ], CSF [ 6 ], BMM [ 8 ], CNR [ 14 ], we use authors’ implementation in experiments.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the performance of our marker-less algorithm is illustrated on the Human3.6M. We compare our approach, which is denoted as TUNS (temporal union of nonlinear subspaces) in the remainder of this section, against six NRSfM baselines: point tracking algorithm PTA [ 5 ], the trajectory-sapce method CSF [ 6 ], the block matrix method BMM [ 8 ], the temporal union of subspaces TUS [ 31 ], the accelerated proximal gradient optimization APG [ 9 ] and the consensus NRSfM of CNR [ 14 ]. For PTA [ 5 ], CSF [ 6 ], BMM [ 8 ], CNR [ 14 ], we use authors’ implementation in experiments.…”
Section: Methodsmentioning
confidence: 99%
“…For PTA [ 5 ] and CSF [ 6 ], we manually set the rank of the subspace to the value yielding the best results. For TUS [ 31 ] and APG [ 9 ], since there are not publicly available implementations, our re-implementations are adopted in comparison. We test such re-implementations and get similar results to what the authors reported in [ 9 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations